2021
DOI: 10.1167/jov.21.11.5
|View full text |Cite
|
Sign up to set email alerts
|

Orienting of covert attention by neutral and emotional gaze cues appears to be unaffected by mild to moderate amblyopia

Abstract: Amblyopia is a developmental disorder of vision associated with higher-order visual attention deficits. We explored whether amblyopia affects the orienting of covert spatial attention by measuring the magnitude of the gaze cueing effect from emotional faces. Gaze and emotion cues are key components of social attention. Participants with normal vision (n = 30), anisometropic (n = 7) or strabismic/mixed (n = 5) amblyopia performed a cued peripheral target detection task under monocular and binocular viewing cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 119 publications
(228 reference statements)
0
2
0
Order By: Relevance
“…Although previous studies in typically developing individuals have reported mixed findings when static facial expressions were the cue stimuli, there is increasing evidence that dynamic facial expressions, changing from neutral to emotional expressions, can modulate the magnitude of the gaze-cueing effect (see Dalmaso et al, 2020 for review). In particular, dynamic fearful faces induce an enhanced gaze-cueing effect compared with neutral faces ( Tipples, 2006 ; Uono et al, 2009a ; Graham et al, 2010 ; Lassalle and Itier, 2013 , 2015b ; Neath et al, 2013 ; Dawel et al, 2015 ; McCrackin and Itier, 2018 ; Chow et al, 2021 ; but see Bayless et al, 2011 ) and other emotional faces ( Putman et al, 2006 ; Bayless et al, 2011 ; Neath et al, 2013 ; McCrackin and Itier, 2018 , 2019 ; Chow et al, 2021 ; however, see Fichtenholtz et al, 2007 , 2009 ; Graham et al, 2010 ; Lachat et al, 2012b ; Uono et al, 2009a ; Lassalle and Itier, 2015a , b ). Evidence suggests that angry ( Lassalle and Itier, 2013 , 2015b ; Pecchinenda and Petrucci, 2016 ; Liu et al, 2019 ) and happy faces ( Graham et al, 2010 ; McCrackin and Itier, 2018 , 2019 ) can enhance the gaze-cueing effect compared to neutral faces, although the enhancement could be less than with fearful faces ( Uono et al, 2009a ; McCrackin and Itier, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies in typically developing individuals have reported mixed findings when static facial expressions were the cue stimuli, there is increasing evidence that dynamic facial expressions, changing from neutral to emotional expressions, can modulate the magnitude of the gaze-cueing effect (see Dalmaso et al, 2020 for review). In particular, dynamic fearful faces induce an enhanced gaze-cueing effect compared with neutral faces ( Tipples, 2006 ; Uono et al, 2009a ; Graham et al, 2010 ; Lassalle and Itier, 2013 , 2015b ; Neath et al, 2013 ; Dawel et al, 2015 ; McCrackin and Itier, 2018 ; Chow et al, 2021 ; but see Bayless et al, 2011 ) and other emotional faces ( Putman et al, 2006 ; Bayless et al, 2011 ; Neath et al, 2013 ; McCrackin and Itier, 2018 , 2019 ; Chow et al, 2021 ; however, see Fichtenholtz et al, 2007 , 2009 ; Graham et al, 2010 ; Lachat et al, 2012b ; Uono et al, 2009a ; Lassalle and Itier, 2015a , b ). Evidence suggests that angry ( Lassalle and Itier, 2013 , 2015b ; Pecchinenda and Petrucci, 2016 ; Liu et al, 2019 ) and happy faces ( Graham et al, 2010 ; McCrackin and Itier, 2018 , 2019 ) can enhance the gaze-cueing effect compared to neutral faces, although the enhancement could be less than with fearful faces ( Uono et al, 2009a ; McCrackin and Itier, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, higher-level deficits in attention, visual search or executive function were demonstrated in adults [58][59][60][61][62][63][64] and children [65] with amblyopia. However, not all aspects of attentional processing are affected, such as for example covert attention [66][67][68]. The pattern of visual deficits varies with the type of amblyopia [69], but in general, individuals with strabismic amblyopia tend to have poorer binocular vision than those with anisometropic amblyopia [69,70].…”
Section: Binocular Visual Function: Summation and Fusionmentioning
confidence: 99%